ESG Disclosure Model and Financial Performance: ThThe Mediating Role of Leader Exemplarity in Sustainable Organizations - Sitorus, Anggi Pratiwi; Siregar, Saparuddin; Nurlaila (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this research is to investigate how implementing Environmental, Social, and Governance (ESG) in a planned, measured, and sustainable manner might improve the performance of the OJK in Indonesia. A quantitative technique is used in this associative research. The quantitative approach focuses on the numerical measurement of study variables and data analysis using static processes and systematic modelling to investigate parts, phenomena, and relationships. From the beginning to the end, this quantitative research method is specific and well-planned. In environmental, social and governance (ESG) performance was found to be positively correlated with financial success among companies included in the Jakarta Islamic Index Indonesia (JII). Although the leadership quality of companies listed on JII is positively correlated with environmental and social performance, this quality is not significantly correlated with governance performance. The presence of the leadership variable as a variable that moderates ESG disclosure on enhancing firm financial performance as evaluated by the capped free float index or the weight of company shares listed on the Jakarta Islamic Index is novel in this study.